(untitled) (Global Journal of Human-Social Science, 2016)
In a study with N = 204 participants, artists (painters) demonstrated significantly higher levels of the trait of Engagement with Beauty than non-artists (medium effect size). Artists also showed significantly higher levels of trait Happiness than non-artists (small effect size). There appear to be no published studies comparing artists’ and non-artists’ levels of the trait of Engagement with Beauty nor trait Happiness. There was no difference in levels of engaging with moral beauty between artists and non-artists; but artists scored significantly higher on engagement with natural beauty (medium effect size), and engagement with artistic beauty (large effect size). The correlations between Engagement with Beauty and trait Happiness, and with Openness, were both positive and significant. However, artists showed no relationship between Openness and Happiness, whereas nonartists did; and the correlation between Engagement with Beauty and Happiness remained significant when controlling for Openness.